2018
DOI: 10.1002/ejic.201800663
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Solar Light H2 Production by Aqueous Glucose Reforming

Abstract: A series of tungsten and nitrogen doped Pt-TiO 2 samples were prepared with the aim to extend the TiO 2 absorption to the visible light region and to enhance the separation efficiency of the photogenerated electron/hole pairs. The physicochemical features of the powders were characterized by Xray diffraction (XRD), UV/Vis reflectance spectra, specific surface area (SSA) determinations, and transmission electron microscopy (TEM) analyses. The influence of the presence of different [a] "Schiavello

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…This conversion operated under solar light irradiation (for 120 min) was comparable with the conversion by nanoparticles reported by Bellardita et al . They used Pt-TiO 2 nanoparticles as the photocatalysts, wherein the highest glucose conversion of 62.1% was achieved after operation under solar light for 360 min . In addition, in this work, it was found that arabinose was detected as the main product, which exhibited a percentage of 24%.…”
Section: Resultssupporting
confidence: 87%
“…This conversion operated under solar light irradiation (for 120 min) was comparable with the conversion by nanoparticles reported by Bellardita et al . They used Pt-TiO 2 nanoparticles as the photocatalysts, wherein the highest glucose conversion of 62.1% was achieved after operation under solar light for 360 min . In addition, in this work, it was found that arabinose was detected as the main product, which exhibited a percentage of 24%.…”
Section: Resultssupporting
confidence: 87%
“…[89,97]. Bellardita et al doped N and W into the lattice of TiO 2 using a hydrothermal method and further surface modified by Pt [88]. It was found that hydrogen production rate on Pt/(N and W)-TiO 2 in photocatalytic reforming of glucose under natural solar light was as high as 1.0 mmol h −1 g cat −1 .…”
Section: Photocatalytic Reforming Of Biomassmentioning
confidence: 99%
“…As it is reported that the presence of Ti 3+ species in the TiO 2 matrix enhances the hydrogen production under visible light [84], runs in the presence of the sample F/Ti = 0.25 (the most coloured one) were carried out in a closed system under visible light irradiation by using formic acid as the sacrificial agent [6]. After 4 h of irradiation, a formic acid conversion of ca.…”
Section: Resultsmentioning
confidence: 99%
“…In the last 50 years, heterogeneous photocatalysis has developed in the field of environmental clean-up [1][2][3][4], conversion of solar energy and fuels production [5][6][7], and synthesis of high value added compounds [8][9][10][11][12]. Although a great interest was recently devoted to alternative photocatalysts [13][14][15][16], the most used one remains TiO 2 [5,17,18].…”
Section: Introductionmentioning
confidence: 99%